European codification system of the causes and circumstances of accidents at work (Office for Official Publications of the European Communities, 2000)
The publication focuses on European classification of accidents and injuries that occur at work and presents guidelines for using them to improve the safety of workers. Intended for professional public.
Employment & social affairs. Health and safety at work
Keywords: Occupational Health; směrnice jako téma; Evropa; Europe; pracovní nehody; klasifikace; Accidents, Occupational; Accident Prevention; hygiena práce; pracovní lékařství; prevence úrazů; Occupational Injuries; Classification; European Union; pracovní úrazy; Evropská unie; Guidelines as Topic